2020
DOI: 10.3390/pharmaceutics12070656
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Delivered HIV Peptides to Dendritic Cells a Promising Approach to Generate a Therapeutic Vaccine

Abstract: Finding a functional cure for HIV-1 infection will markedly decrease the social and economic burden of this disease. In this work, we have taken advantage of the antigen presenting cell role of human dendritic cells (DCs) to try to induce an immune response to HIV-derived peptide delivered to DCs using two different polycationic nanoparticles: a G4 PAMAM dendrimer modified to a 70/30 ratio of hydroxyl groups/amines and a cyclodextrin derivative. We have studied peptide delivery using a fluorescence peptide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is advantageous to use NP formulations to enhance and improve the bioavailability of aptamers. , Applying NP formulations for peptide delivery and presentation to immune cells has been explored in multiple works. For example, in 2020, Martín-Moreno et al showed that the effect of peptide vaccines can be boosted by attaching the peptide to a dendrimer-based NP . The NP allows for a low-dose, s.c. administration and thereby a controlled, slow release of the aptamer to the blood.…”
Section: Discussionmentioning
confidence: 99%
“…It is advantageous to use NP formulations to enhance and improve the bioavailability of aptamers. , Applying NP formulations for peptide delivery and presentation to immune cells has been explored in multiple works. For example, in 2020, Martín-Moreno et al showed that the effect of peptide vaccines can be boosted by attaching the peptide to a dendrimer-based NP . The NP allows for a low-dose, s.c. administration and thereby a controlled, slow release of the aptamer to the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study uses G4-70/30 PAMAM polycationic dendrimer and AMC6 nanoparticle derived from β-cyclodextrin as peptide delivery agents ( 175 ). In this work, an antigenic peptide derived from the HIV-1 gag p24 protein was used in combination with these polycationic structures, binding to specific receptors.…”
Section: Nanoparticles In Dcs Vaccinesmentioning
confidence: 99%
“…Polycationic cyclodextrins have become the iconic representatives in this category [ 5 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. The efficiency in compacting nucleic acids into nanocomplexes (so-called CDplexes) capable of mediating cell entry and subsequent expression of the nucleic acid anticipated activity (transfection) was significantly enhanced for prototypes that can additionally establish cyclodextrin–cyclodextrin interactions through either hydrophobic [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ], host–guest [ 79 , 134 ] or aromatic–aromatic contacts [ 135 , 136 , 137 , 138 , 139 , 140 , …”
Section: Biomacromolecule-templated Formation Of Functional Glycocmentioning
confidence: 99%